Aquatic and terrestrial resources are not nutritionally reciprocal for consumers. (19th July 2019) - Twining, Cornelia W.; Brenna, J. Thomas; Lawrence, Peter; Winkler, David W.; Flecker, Alexander S.; Hairston, Nelson G.
Abstract: Aquatic and terrestrial ecosystems are connected through reciprocal fluxes of energy and nutrients that can subsidize consumers. Past research on reciprocal aquatic–terrestrial subsidies to consumers has generally focused on subsidy quantity while ignoring major differences in the nutritional composition of aquatic and terrestrial resources. Because aquatic resources contain substantially more highly unsaturated omega‐3 fatty acids (HUFAs) than terrestrial resources, aquatic subsidies may play a unique role by supplying these critical compounds to both aquatic and terrestrial consumers. Here, we first characterized nutritional quality in terms of HUFA content in aquatic and terrestrial insect prey. We then used bulk stable isotope analyses to estimate subsidy use by stream and riparian consumers coupled with compound‐specific stable isotope analyses, which allowed us to document consumer HUFA sources. Finally, in order to understand the nutritional importance of aquatic‐derived HUFAs for riparian consumers, we conducted manipulative diet experiments on Eastern Phoebe ( Sayornis phoebe ) chicks in the laboratory. Aquatic insects were significantly enriched in HUFAs, mainly in terms of eicosapentaenoic acid (EPA), compared with terrestrial insects. Stream fishes relied mainly upon aquatic resources, while insectivorous birds varied in their use of aquatic subsidies across sites. However, like stream fishes, Eastern Phoebe chicks received HUFAs from aquatic insects, even when they were heavily reliant upon terrestrial insects for their overall diet. In the laboratory, dietary HUFAs, such as those supplied by aquatic insects, increased the growth rate and condition of Eastern Phoebe chicks. This study demonstrates that aquatic and terrestrial subsidies are not nutritionally reciprocal from the perspective of consumers because aquatic resources are the main source of critical fatty acids for both stream and riparian consumers. It also confirms previous findings on the nutritional importance of HUFAs for riparian birds, demonstrating that an insectivorous riparian lifestyle influences avian nutritional needs. Finally, our findings raise the possibility that birds and other riparian insectivores may experience nutritional mismatches with terrestrial prey if they do not have access to high‐quality aquatic subsidies as a consequence of aquatic habitat degradation or shifts in consumer and resource phenology. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.